2018
DOI: 10.18203/issn.2455-4510.intjresorthop20185331
|View full text |Cite
|
Sign up to set email alerts
|

Thoraco lumbar spinal tuberculosis-assessment of functional outcome following posterior decompression and posterior instrumentation

Abstract: <p class="abstract"><strong>Background:</strong> Spinal tuberculosis is the most common form of extra pulmonary tuberculosis. Complications of untreated spinal tuberculosis include neurological deficit and gibbus deformity. Treatment of spinal TB can be surgical or conservative. Surgical treatment is the mainstay in spinal tuberculosis with neurological deficit. Various approaches to surgical management are anterior only, combined anterior &amp; posterior and posterior only. Posterior onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sundaram et al at Tamil Nadu, found that single stage posterior decompression and instrumentation is a safe and effective procedure in the treatment of tuberculous spondylodiscitis with neurological deficit and a kyphotic angle <60°. 22 Gupta et al at Jodhpur, found that the posterior approach has better correction of the deformity combined with a decreased blood loss and low morbidity. 23 Patidar et al at Ujjain, Madhya Pradesh, concluded that single-stage posterior-only procedure is safe and effective for management of thoracolumbar spinal TB.…”
Section: Resultsmentioning
confidence: 99%
“…Sundaram et al at Tamil Nadu, found that single stage posterior decompression and instrumentation is a safe and effective procedure in the treatment of tuberculous spondylodiscitis with neurological deficit and a kyphotic angle <60°. 22 Gupta et al at Jodhpur, found that the posterior approach has better correction of the deformity combined with a decreased blood loss and low morbidity. 23 Patidar et al at Ujjain, Madhya Pradesh, concluded that single-stage posterior-only procedure is safe and effective for management of thoracolumbar spinal TB.…”
Section: Resultsmentioning
confidence: 99%